Arabidopsis exocyst subcomplex containing subunit EXO70B1 is involved in autophagy-related transport to the vacuole - Kulich, Ivan; Pečenková, Tamara; Sekereš, Juraj; Smetana, Ondřej; Fendrych, Matyáš; Foissner, Ilse; Höftberger, Margit; Zárský, Viktor (Traffic (Copenhagen, Denmark), 2013)
Autophagic transport to the vacuole represents an endomembrane trafficking route, which is widely used in plants, not only during stress situations, but also for vacuole biogenesis and during developmental processes. Here we report a role in autophagic membrane transport for EXO70B1--one of 23 paralogs of Arabidopsis EXO70 exocyst subunits. EXO70B1 positive compartments are internalized into the central vacuole and co-localize with autophagosomal marker ATG8f. This internalization is boosted by induction of autophagy. Loss of function (LOF) mutations in exo70B1 cause reduction of internalized autopagic bodies in the vacuole. Mutant plants also show ectopic hypersensitive response (HR) mediated by salicylic acid (SA) accumulation, increased nitrogen starvation susceptibility and anthocyanin accumulation defects. Anthocyanin accumulation defect persists in npr1x exo70B1 double mutants with SA signaling compromised, while ectopic HR is suppressed. EXO70B1 interacts with SEC5 and EXO84 and forms an exocyst subcomplex involved in autophagy-related, Golgi-independent membrane traffic to the vacuole. We show that EXO70B1 is functionally completely different from EXO70A1 exocyst subunit and adopted a specific role in autophagic transport.
Keywords: proteiny huseníčku; Salicylic Acid; autofagie; mutace; EXO70B1; Arabidopsis; anthokyaniny; Nitrogen; salicylic acid; hypersensitive response; Arabidopsis Proteins; vakuoly; EXO70; Vacuoles; Vesicular Transport Proteins; exocyst; autophagy; Autophagy; kyselina salicylová; Golgi-independent; vezikulární transportní proteiny; dusík; Protein Transport; Anthocyanins; Mutation; transport proteinů